INDEXING POLICY IN ARCHIVES OF HEALTH INSTITUTIONS - Fujita, Mariângela Spotti Lopes; Rodriguez, Sonia Maria Troitiño (Informação em Pauta, 2018)
Indexing is an operation that, in order to be successful in representation and retrieval, depends on the definition of a policy that, for its elaboration and implementation, needs to assess the institution context through requirements for the definition of influential elements and variables in both indexing and retrieval. Among these elements is the controlled vocabulary and the indexing process that will provide specificity and / or exaustivity. However, above all, it is necessary to debate and reflect on the applicability of indexing and indexing policy in records management in the archival area of health institutions. This work, which is an essay feature, proposes an approach on the relationship between records management and indexing policies, with the objective of reflecting on the applicability of indexing policy formulation and implementation within public health institutions in Brazil. The development of the proposed indexing policy applied to the archives of health institutions reveals innovation to the national health network and the need to develop methodologies of information representation within a policy established in line with the needs of informational retrieval of the organization.